The Overview of Algorithms Implementation in File Search Applications or Digital Archives - Hanifah Permatasari; Triyono Triyono; Eko Purwanto (IJEEIT : International Journal of Electrical Engineering and Information Technology, 2023)
As time goes by, the number of documents or files or archives in a company continues to increase. These files are in the form of data collection, activity reports, accountability reports, work proposals, letters, decrees, regulations, and so on. At first, the company tried to convert paper-based files into digital files, then took advantage of several free platforms to store them. Furthermore, companies find it difficult to control digital files because of the non-centralized storage. Finally, companies are trying to create various information systems that allow them to centrally manage digital files. A large number of digital files in it makes the search process even longer, so it is necessary to optimize the search features. The purpose of this study is to review several algorithms that have been implemented to optimize file searches in previous studies. This research takes Indonesian scientific articles from Google Scholar from 2015 to 2022. The result of this research is the explanation of the use of algorithms in previous studies so that this research can become a reference and suggestion for further research. This study found the fact that every information system or application that functions to manage company files or archives requires a search algorithm to improve system performance